Türk rekabet hukukunda uzlaşma - Özyıldırım Ünlü, Betül (My University, 2025)
Bu çalışma, Türk rekabet hukukuna kazandırılan uzlaşma kurumunu tüm yönleriyle incelemektedir. Tezin amacı, soruşturma süreçlerini hızlandırmak ve rekabetin etkinliğini artırmak amacıyla getirilen bu kurumun hukuki niteliğini, uygulama esaslarını ve sonuçlarını analiz etmektir. Çalışmada, uzlaşmanın genel çerçevesi, rekabet hukuku açısından sağladığı avantajlar (hem otorite hem de teşebbüsler için), hukuki niteliğine dair farklı görüşler, unsurları ve türleri ele alınmıştır. Türk hukukundaki yeri, uluslararası uygulamalarla karşılaştırılarak değerlendirilmiştir. Uzlaşma sürecinin aşamaları detaylandırılmış ve Türk Rekabet Kurulunun ilk uzlaşma kararları incelenmiştir. Tezin ağırlıklı kısmını oluşturan hukuki sonuçlar bölümünde ise, ihlal tespiti, para cezası indirimi ve özellikle yargı yolunun kapanmasının hukuki etkileri, anayasal açıdan değerlendirmeler ve yargısal denetim hakkı tartışmaları derinlemesine incelenmiştir. Özellikle Rekabetin Korunması Hakkında Kanun’un 43. maddesi ve Uzlaşma Yönetmeliği çerçevesinde düzenlenen uzlaşma prosedürü hem teorik hem de uygulamalı olarak değerlendirilmiştir. Ayrıca uzlaşma sürecindeki gizlilik ve uzlaşma sağlanamaması halleri de ele alınmıştır. Tez, uzlaşmanın etkin bir araç olma potansiyeli taşıdığını ancak özellikle yargısal denetimden feragat boyutuyla hukuki güvenlik ve şeffaflık gerektiren hassas bir kurum olduğunu sonucuna ulaşmıştır. Rekabet Hukuku, Uzlaşma, Ceza İndirimi, Rekabet Kurumu, Yargısal Denetim.

This Master's Thesis examines the settlement procedure introduced into Turkish competition law from all its aspects. The aim of the thesis is to analyze the legal nature, implementation principles, and consequences of this procedure, which was introduced to accelerate investigation processes and enhance competition effectiveness. The study covers the general framework of settlement, its advantages in terms of competition law (for both the authority and undertakings), different views on its legal nature, its elements, and types. Its place in Turkish law has been evaluated by comparing it with international practices. The stages of the settlement process have been detailed and the initial settlement decisions of the Turkish Competition Authority have been examined. In the legal consequences section, which constitutes the main part of the thesis, the legal effects of infringement determination, fine reduction, and especially the preclusion of judicial review have been examined in depth, along with constitutional evaluations and discussions on the right to judicial review. The settlement procedure regulated particularly within the framework of Article 43 of the Law on Protection of Competition and the Settlement Regulation has been evaluated both theoretically and practically. Furthermore, confidentiality during the settlement process and situations where settlement is not reached have also been addressed. The thesis concludes that settlement has the potential to be an effective tool but is a sensitive institution requiring legal certa!nty and transparency, particularly due to the aspect of waiving judicial review
Keywords: Competition; Compromise (Law); Law and legislation; Rekabet; Turkey; Türkiye; Uzlaşma (Hukuk); Yasa ve yasama